2014
DOI: 10.1016/j.bjid.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of blood stream infection and antibiotic resistance in intensive care unit at a tertiary care hospital in North India

Abstract: High frequencies of multidrug resistant organisms were observed in intensive care units which is a warning as to use the only few effective antimicrobials wisely to reduce selective pressure on sensitive strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 30 publications
15
37
1
Order By: Relevance
“…Our data also showed that there were more Gram-negative (50.96%) than Gram-positive isolates (49.04%), an observation very similar to that stated earlier by Wattal et al 14 This is not surprising since the former are known to develop resistance more rapidly and extensively than the latter. 15 Among the gram positive isolates, Coagulase negative staphylococci (CoNS) was the most common blood culture isolate (35.58%) in this study (Figure 2).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Our data also showed that there were more Gram-negative (50.96%) than Gram-positive isolates (49.04%), an observation very similar to that stated earlier by Wattal et al 14 This is not surprising since the former are known to develop resistance more rapidly and extensively than the latter. 15 Among the gram positive isolates, Coagulase negative staphylococci (CoNS) was the most common blood culture isolate (35.58%) in this study (Figure 2).…”
supporting
confidence: 92%
“…Even among Gram negative bacteria, resistance to Beta lactams or combination of Beta lactams with Beta lactamase inhibitors was a dominant feature ( Table 2). The gram negative bacteria were however sensitive to Aminoglycosides, Colistin and Tigecycline to a variable extent, a trend very similar to that documented by Wattal et al 14 Authors found that Klebsiella pneumoniae was resistant to most of the commonly prescribed antibiotics like Piperacillin -Tazobactam, Meropenem, Amikacin and Tigecycline (Table 2). Authors also found that among the gram negative isolates, Klebsiella pneumoniae and Acinetobacter species have emerged as problematic species in this ICU.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…This result is found consistent with other studies [20][21][22]. CNS is member of the indigeneous micribiota of healthy peoples.…”
Section: Focus Of Infection Are Not Identified At Primary Bsis Likewisesupporting
confidence: 94%
“…Also in this study, S. aureus and E.coli isolated from blood stream infections were detected more frequently in non ICU patients than ICU cases [20]. In another study conducted, 2846 positive samples isolated from blood cultures in ICU at a tertiary care hospital in North India were analysed by Wattal et al [21] and in their study CNS was the most prevalent pathogens isolated from blood cultures in ICU patients followed by Candida spp. in 20.3% and 17.5% respectively.…”
Section: Focus Of Infection Are Not Identified At Primary Bsis Likewisementioning
confidence: 50%